SELECTED ASPECTS OF MOTIVATION IN WORKING SENIORS WITH ICT - VYBÍRAL, Petr; HODIS, Zdeněk (Trends in education, 2014)
The contribution deals seniors motivational factors at work with information and communication technologies. On the basis of qualitative research results of the survey are presented in the form of case studies.
Keywords: senior; information technology; motivation; U3V.